Investigation on Administration Schedule Practice of Hypnotic Drugs of Outpatients - MIURA, TAMAO; ISHIZAWA, FUMIAKI; ONUKI, HIROMI; YONEZAWA, KENZO; SUGAWARA, YASUNORI; TANAKA, EMIKO; YAMAGUCHI, ISAMU (Byōin yakugaku, 1992)
The present study was designed to investigate on administration schedule practice of hypnotic drugs for outpatients.One hundred and sixty-three outpatients were interviewed at the dispensing counter.They consisted of 53 males (range of 46-86 years) and 110 females (range of 33-88 years).Of the 53 male group, 27 were given triazolam, and 11 were given zopiclone.Of the 110 female group, 69 were given triazolam, and 16 were given estazolam.All outpatients were classified as the following 4 patterrs according to the administration schedule practice of the drugs:(1) who have been taking hypnotic drugs as directed, (2) who have reduced a dose of it and have been taking it as directed, (3) who have sometimes been taking as directed, and (4) who have reduced a dose and have sometimes been taking.As the result of this study, about 36% of male and 53% of female outpatients have been taking hypnotic drugs under the circumctances that they only felt in need at bedtime and 34% of male and 44% of female outpatients have reduced a dose and have been taking at bedtime.